French subject doubling - Yiming Liang; Caterina Donati; Heather Burnett (Isogloss)
This paper revisits the status of subject clitics in Spoken French by studying subject doubling as a sociolinguistic variable. In the literature, two influential analyses have been proposed to account for French subject doubling. Based on new evidence from a corpus study on the large Multicultural Paris French (MPF) corpus, we argue for an analysis reconciling these two competing views of the construction in Spoken (colloquial) French. On one hand, we provide further support to the morphological approach (Auger, 1994; Culbertson, 2010) in which subject clitics are morphological agreement markers on the verb. On the other hand, we argue based on new evidence that lexical subjects are topicalized, as in the dislocation analysis. Furthermore, we argue that Spoken French is in a diglossia situation where speakers alternate structures provided by both Standard French and Colloquial French grammars. This paper provides further evidence of how quantitative studies of language use can shed light on long-standing theoretical debates.